Identity construction through schooling: listening to students’ voices - Freire, Sofia (2012)
Nowadays, one of the main problems faced by several educational systems around the world is educational exclusion. Portugal is no exception. It is recognized that those who drop out education are at risk of social exclusion, with reduced opportunities to participate in the society. In order to understand it, we reconceptualised school as a community of practice, where students not only appropriate academic knowledge, but also new ways of being and perceiving themselves and the others and school practice itself. With this article, we aim at better understanding educational exclusion from the perspective of at-risk students. How does their constructed positional identities originate ways of being, relating and acting in relation to school agents and practices? We developed four focus group interviews with students presenting high rates of truancy and failure (N=20). Against our expectations several students showed intend of pursuing their own path within the school system and see themselves as able of changing the conditions of failure in order to succeed in school.